A Feasibility study on the production of lemon soap - Anunciacion, Herbert N.; Berena, Edith S.; Diaz, Edgar Z.; Tensuan, Michael D. (Diliman, Quezon City College of Engineering, 1978)
Resources Plus, Incorporated is a corporation to be established in 1978, composed, primarily of the proponents of this project and an unlimited and variable number of shareholders. The corporation is producing Lemon Fresh, a lemon-scented toilet soap to be introduced into the market at the early part of 1979. Its head office and plant site is at Rosario, Cavite. This study made to gauge the feasibility of marketing a new product, lemon soap, its production, and the financial stability of this endeavor. In as much as exact figures are impossible to obtain, the group opted for the closest estimates available, and adjusted accordingly as deemed fitting. Throughout the study, a conservative point of view has been taken and the risk factor introduced quite substantially. In generating conclusions, projections ,and otherwise unquantifiable factors, a set of assumptions have been made which have all been in keeping with the attitude the group wishes to maintain towards this project. The reader would find these assumptions at the start of each section. After the study, the conclusion drawn is that in all three aspects, the project is feasible and viable. The technical data shows that the company has enough capacity to meet the projected demand up to the tenth year if production is extended to two shifts per day at a maximum level. Financial analysis shows that the plant expansion on the tenth year is possible. However, at this point, the proponents should conduct a cost-benefit analysis, considering that the demand is approaching a constant level due to its exponential nature. This has a bearing on the product's life cycle and aside from physical expansion necessary to accommodate increased capacity, product line diversification may be resorted to. As to the technical aspect, the conclusion is that the project is feasible due to the availability of all the equipment and the competitive nature of these equipments in terms of price. The trends in research and development can always come up with innovations which will aid the marketing function of the company.
Feasibility study
Typescript
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: Resources Plus, Incorporated; Lemon trade; Soap; Participatory monitoring and evaluation (Project management)